Study on an SIR rumor propagation model with an interaction mechanism on WeChat networks - Chang, Xinghua (Frontiers in Physics, 2023)
The spread of rumors does great harm to society. It will not only disrupt social order, but also damage public interests, and even cause public safety and social shock. With the development of social platforms, it has become a fertile ground for rumors to breed and spread. WeChat group as a very popular social platform is an important medium of rumor spreading with the accurate and fast characteristics. In this paper, in order to describe the dynamic characteristics of rumors spread in WeChat groups, an SIR rumor propagation model with interaction mechanism and population dynamics on WeChat groups is proposed. In order to analyze the dynamic characteristics of the system, the next generation matrix method is used to calculate the basic reproduction number of the proposed model. Then the stability of a disease-free equilibrium point and a positive equilibrium point of the system are analyzed in detail. Finally, the accuracy of the analysis results is verified by numerical simulation. The research results are of great significance for controlling rumors spread in WeChat groups.